2006
DOI: 10.2298/sos0601007r
|View full text |Cite
|
Sign up to set email alerts
|

Frenkel's theory of sintering

Abstract: Principles of Frenkel's Theory of Sintering are presented in this paper. This theory represents the first physical theory of sintering, in which sintering takes place in two stages as a consequence of "viscous" flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 1 publication
0
30
0
2
Order By: Relevance
“…Sintering is a process by which the surface of a material is reduced by mass transport [12,[22][23][24]. In a previous work [22], we showed that two types of mechanisms are responsible for sintering.…”
Section: Sintering Of Aerogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sintering is a process by which the surface of a material is reduced by mass transport [12,[22][23][24]. In a previous work [22], we showed that two types of mechanisms are responsible for sintering.…”
Section: Sintering Of Aerogelsmentioning
confidence: 99%
“…In the intermediate temperature range, both processes exist and overlap. The viscous flow mechanism and the determination of its activation energy were identified based on the Frenkel model [24]. However, because of the approximations concerning its geometry, the Frenkel model should not be used after first stages of sintering.…”
Section: Sintering Of Aerogelsmentioning
confidence: 99%
“…The theoretical models that describe the initial stage of sintering are based on the coalescence of two tangent spheres. [27][28][29][30][31][32][33] With these models, the problem of complex geometry of powders is reduced to a much simpler one. Two types of sintering mechanisms can be involved in the neck growth as described by the two-spheres sintering model ( Fig.…”
Section: Theorymentioning
confidence: 99%
“…Typically, flashes of light of a broad emission spectrum and with a peak in the ultraviolet wavelength range are used. The radiation is absorbed by metal particles which results in a sintering process [21][22][23][24] mainly controlled by the intensity of the radiation and its duration [11]. Additionally, metal particle size and shape plays a role for sintering behaviour.…”
Section: Photonic Sinteringmentioning
confidence: 99%